2011
DOI: 10.1038/cdd.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhibition of TAK1 protects against neuronal death in cerebral ischemia

Abstract: Neuronal apoptosis contributes to ischemic brain damage and neurodegenerative disorders. Key regulators of neuronal apoptosis are the transcription factor NF-jB and the MAP kinases p38/MAPK and JNK, which share a common upstream activator, the mitogen-activated protein kinase kinase kinase (MAP3K) TGFb-activated kinase 1 (TAK1). Here we investigate the function of TAK1 in ischemia-induced neuronal apoptosis. In primary cortical neurons, TAK1 was activated by oxygen glucose deprivation (OGD), an in vitro model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 40 publications
4
68
1
Order By: Relevance
“…Combining tissue-specific and inducible deletion systems, we found that both acute and sustained loss of TAK1 resulted in an extensive apoptotic death of DCs. This result contrasted with the observations in neuronal cells in which short-term inhibition of TAK1 protects neurons from apoptosis, whereas prolonged inhibition is not protective (61). Therefore, our findings indicate a direct effect of TAK1 to actively maintain DC survival.…”
Section: Discussioncontrasting
confidence: 99%
“…Combining tissue-specific and inducible deletion systems, we found that both acute and sustained loss of TAK1 resulted in an extensive apoptotic death of DCs. This result contrasted with the observations in neuronal cells in which short-term inhibition of TAK1 protects neurons from apoptosis, whereas prolonged inhibition is not protective (61). Therefore, our findings indicate a direct effect of TAK1 to actively maintain DC survival.…”
Section: Discussioncontrasting
confidence: 99%
“…The activated TAK1 in turn activates the NF-B and MAPK pathways (13,14). Recent investigations also demonstrate that inhibition of TAK1 provides neuroprotection in ischemia and traumatic brain injury (15)(16)(17). Taking into account this background, the present study aimed to evaluate whether TAK1 is activated after SAH.…”
Section: Subarachnoid Hemorrhage (Sah)mentioning
confidence: 98%
“…Several studies have reported that TAK1 is a critical regulator of apoptosis, which is mainly mediated by the downstream pathways of p38 MAPKK, JNK, ERK-1/2, and NF-B p65 (15,16,37). Evidence shows that activation of MAPK and NF-B pathways contributes to EBI after SAH, and inhibition of these pathways offer neuroprotective effects against SAH (5, 24, 26).…”
Section: Tak1 Inhibition Attenuates Early Brain Injury After Sahmentioning
confidence: 99%
“…Consistent with this study, TAK1 blockage formed more ROS in response to LPS stimulation in neutrophils, indicating that TAK1 is a negative regulator of ROS production (Omori et al 2008). However, recent studies have shown that pharmacological blockade or genetic ablation of TAK1 causes a drastic reduction in ROS production such as superoxide formation in vascular smooth muscle cells and neurons (Song et al 2014;Neubert et al 2011). Herein, the enhancement of superoxide formation by 5Z-7-oxozeaenol might be essential for the apoptotic enhancement after HT treatment.…”
Section: Discussionmentioning
confidence: 98%